THE INTER-AMERICAN SYSTEM OF HUMAN RIGHTS AND THE RIGHT OF ACCESS TO PUBLIC INFORMATION IN THE JURISPRUDENCE OF THE INTER-AMERICAN COURT OF HUMAN RIGHTS - Janampa Almora, Juan José (2020)
This paper intends to inform the functioning of the Inter-American Human Rights System and its main institutions such as the Inter-American Court of Human Rights and the Inter-American Commission on Human Rights. In this sense, it will be evaluated how the Inter-American System has been working in relation to the right of access to public information as a fundamental tool for the control of citizenship against authority and as a institution for the strengthening of democracy.Inter-American Court of Human Rights - Inter-American Commission on human rights - right of access to public information - citizenship – democracy